Benthic Chamber Lander stable isotope tracer experiments in the Cabo Verde Abyssal Basin (tropical East Atlantic) - Danielle de Jonge; Daniela Y Gaurisas; Alycia J Smith; Eloise Holmes; Covadonga Orejas; Ángela Mosquera Giménez; J Murray Roberts; Angelo Bernadino; Andrew K Sweetman (PANGAEA, 2024)
A total of five deployments of a Benthic Chamber Lander were conducted at the Cabo Verde Abyssal Plain (tropical East Atlantic) at about 4200 m water depth. The deployments took place from the research vessel Sarmiento de Gamboa during the iMirabilis2 campaign in August 2021. Each deployment carried three functional chambers, one conducting a stable isotope tracer experiment, and two collecting background data. The stable isotope tracer used was axenically cultured and lyophilised diatoms (Phaeodactylum tricornutum) labelled with 13C and 15N. The experiment had a duration of 48 hours. The chamber carried an oxygen optode (Aanderaa 4330F) for continuous oxygen concentration measurements used to determine sediment community oxygen consumption (SCOC). During the experiment seven water samples were collected at hours T0.33, T2, T10, T19, T28, T37, and T46. The water samples were processed for oxygen concentration (Micro-Winkler Titration) as a second method to determine SCOC, Dissolved Inorganic Carbon (DIC and DI13C) concentration in order to calculate the substrate-derived respiration rate, and nutrients (NH4, NO2, NO3, PO4, Si) concentrations to determine nutrient fluxes. The sediments were sampled after lander recovery. Sediments were analysed for Total Organic Carbon (TOC and TO13C) in order to establish if injection was successful and get a carbon content sediment profile. Sediments were analysed for Phospholipid-derived Fatty Acid (PLFA) biomarkers including their 13C stable isotope signal, in order to calculate bacterial biomass and tracer incorporation during the incubation. Sediment samples for macrofauna, large Foraminifera, and meiobenthos were preserved in 4% buffered formaldehyde, then transferred to ethanol, until analysis. Meiobenthos was extracted using LUDOX density separation and a 32 μm mesh, and identified to extquotesingleNematoda extquotesingle and extquotesingleOther meiobenthos extquotesingle for the 0-2 and the 2-5 cm sediment horizons, in order to calculate meiobenthic densities. Sediments for macrofauna and large Foraminifera were washed over a 300 μm mesh and picked for identification and determining densities. After identification, samples were dried at 45 °C until stable mass. For calcareous organisms, the sample was acidified, and dried at 45 °C again. Dried samples were analysed for dry mass, carbon and nitrogen content and stable isotope signals (13C, 15N). C and N incorporation rates were calculated from stable isotope signals.